Research on Satisfaction Evaluation and Factors of International Express Service in Laos - CHANGSAVANG, Viphachack; Chaojun, Yang (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
This paper, AHP is used to determine the index weight value, and the service quality of TNT International Express Service Company in Laos is evaluated and analyzed by fuzzy comprehensive evaluation method. Finally, on the premise of customer satisfaction, the service quality of TNT International Express Service Company in Laos is good. According to the results of the questionnaire scores, researchers find the service quality problems of TNT International Express Service Company in Laos that has to deal with many performance items every day, thus it has a lot of housework to solve customers' problems. If it's not serious, it will cause customer dissatisfaction. In terms of types, customers generally agree that the fees of TNT International Express Service Company in Laos are open and reasonable, but it reflects the fact that the fees of TNT International Express Service Company in Laos are higher. This is mainly due to the fact that TNT International Express Service Company in Laos uses air transport to deliver express, which greatly increases the transportation cost. The environment is not sufficient, the staff's clothes are uneven, and some staff are not in a mess. For the sake of guarantee, customers generally believe that TNT International Express Service Company in Laos can quickly deliver and deliver goods within the specified time. But customers are not satisfied with the express delivery points of TNT International Express Service Company in Laos. They think there are several express delivery points. This is a direct selling model of TNT International Express Service Company in Laos, which has a large proportion of combined construction capital, less developed economic development and many remote areas. TNT International Express Service Company s in Laos has no circulating fulcrum, so it can develop opportunities for TNT International Express Service Company in Laos. Laos TNT International Express Service Company distribution management is not standardized, the quality of professionals is low, and the lack of professionals is due to the low technical content of the super distribution industry, high profits of large enterprises, easy access, and full of cheap labor market. The average score of reliability dimension is the lowest. Therefore, TNT International Express service companies in Laos still need to be enhanced their trust. Among them, the postman sometimes divulges the customer's privacy, while the customer is not satisfied with the customer's information confidentiality, and sometimes the postal logistics information will not be updated.